Palavras dissidentes: a exposição ao HIV/AIDS no discurso de um blog de barebacking sex direcionado a homens que tem sexo com outros homens - Almeida Junior, Wilson Nascimento [UNIFESP] (2017)
The term Barebacking is used by the international gay community to name intentional unprotected anal sex among men who have sex with men (MSM). A practice which goes against HIV / AIDS prevention policies and even the idea of self-awareness, so common in today's society. Barebacking can be categorized into what Bourdieu (2010) refers to as Lifestyles, that is, a set of actions and behavior that go against the institutionalized habitus. In this sense, facing the current situation of the AIDS epidemic, the study of Barebacking is urgent, especially through the linguistic economy dismissed by its adherents. It is on the Internet, through pornography websites and blogs followed by the pornographic industry itself, that Barebacking finds its greatest means of expression, with both vehicles being a lucrative source of research. Thus, based on the understanding of Barebacking as a lifestyle (BOURDIEU, 2010), the present work aims to investigate the meaning of exposure to HIV / AIDS from a practice perspective. The material for analysis was composed of written records by followers of a Barebacking Sex blog aimed at MSM, as well as images and symbols common to the practice. The data were analyzed based on the economics of linguistic exchanges as proposed by Bourdieu (2000) and discussed by different authors. The results point to: the Internet as an important linguistic market in the expression that confronts the institutionalized discourse on HIV / AIDS; the junction between risk, pleasure and danger in the constitution of identities and eroticism; exposure to HIV / AIDS as inherent / conscious to the practice of Barebacking, as well as an important aspect of the masculinity power games involved in the practice; and the importance of pornography in the expression of Barebacking, as a means where we have access to the way the practice is organized, or in the relationship between fetish and identity. In conclusion, we note that in its most singular way, Barebacking constitutes a lifestyle that imposes great challenges to the HIV / AIDS prevention policies, especially when eroticism and sexuality are not taken into account and are based on aspects that go against a more general rule of expected and / or institutionalized behaviors.